Representation and Commodification of Female Body in the Indonesian Post Reform Horror Movies - Verena Vinandia Larasati; Abdul Wahid (Asian Journal of Media and Communication, 2020)
This study examines the representation and commodification practices of female bodies in the Indonesian horror films produced in the Post Reform Era. Three horror movies, i.e. Terowongan Casablanca (2007), Tali Pocong Perawan (2008), and Air Terjun Pengantin (2009), have been analyzed with qualitative textual analysis. This study finds that the female body is commodified in the movies through the costumes that show clearly their sexy bodies, the actions and gestures that demonstrate their seductive lust, and the setting of scenes that emphasize their sexual desires. These representations are closely related with the producers backgrounds and track records in the way that they are used to producing horror movies that mostly using sexy woman as lead actress. Keywords: representation, commodification, Indonesian horror movies, female body.